Serat Gatholoco: Tubuh Menggugat Agama - Syihabul Furqon; Busro Busro (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2018)
The new era of Islam is characterized by the interdependence of the modern world that is inaccessible to the presence and primordiality of the full tradition. This opposition is as strong and stubborn as it is always accompanied by criticisms of two trends: excesses to modernity or tradition. The language as an interstitial is made very plastic and allows the thinker, the genius of his day to pour their ideas into their tendencies. Because Pakistan holds its belief, modernity also provides its firmness through language. One of them is in a series of critical religions and elements of vulgar erotic elements: Gatholoco. The contents of the contextual religious debate about time, this fiber, even for the present context, can still be a new direction. Back in touch with orientation and affirmation of the body - not abolished